2006
DOI: 10.4269/ajtmh.2006.74.308
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Clustering and Epidemiological Aspects of Visceral Leishmaniasis in Two Endemic Villages, Baringo District, Kenya

Abstract: Visceral leishmaniasis (VL) seroprevalence in Kenya is unknown because of the lack of a practical and accurate diagnostic test or surveillance system. A novel serological assay was used to estimate the seroprevalence of Leishmania-specific antibodies, and Global Information System and spatial clustering techniques were applied to study the presence of spatial clusters in Parkarin and Loboi villages in Baringo District in 2001. VL seroprevalences were 52.5% in Parkarin and 16.9% in Loboi. Significant associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
8
26
0
1
Order By: Relevance
“…Generally, poor housing construction was found to be characteristics of the study area where visceral leishmaniasis was prevalent and vector density is also high. The reports of earlier workers, also support these findings and have been reported that mud plastered household and cattle shed are suitable for the development of phlebotomine species in Indian sub-continent [16,17], Brazil[18] and Kenya [19] respectively. The largest odds ratios, however, are associated with wall types of the houses.…”
Section: Discussionsupporting
confidence: 73%
“…Generally, poor housing construction was found to be characteristics of the study area where visceral leishmaniasis was prevalent and vector density is also high. The reports of earlier workers, also support these findings and have been reported that mud plastered household and cattle shed are suitable for the development of phlebotomine species in Indian sub-continent [16,17], Brazil[18] and Kenya [19] respectively. The largest odds ratios, however, are associated with wall types of the houses.…”
Section: Discussionsupporting
confidence: 73%
“…Although this may work well on maps that show relatively large geographical units (such as those used in the present study), it may not work as well on a smaller scale, where neighbourhood-level geographical barriers, such as rivers or train tracks, could create non-circular interaction patterns. However, the Spatial Scan Statistics employed in the present study has higher statistical power than other geostatistical methods and has been widely applied to the detection of clustering of diseases [18-21]. …”
Section: Discussionmentioning
confidence: 99%
“…Such differences might reflect not only variations in the magnitude of transmission between these areas but also differences in the diagnostic methods used and the age distribution within the studied population. Ryan et al (2006), while studying two villages in Kenya, found a linear relationship between seroprevalence for VL and age. Because our study included all age groups this feature could be an explanation for the high prevalence reported here.…”
Section: Discussionmentioning
confidence: 99%